Predictors of Violence among Drug Abusers in Selected Drug Joints in Mushin, Lagos Metropolis - Folorunsho Muyideen Ogunmefun (RIRAI Publisher, 2020)
The prevailing incidence of illicit drug intake among youths in Nigeria is alarming and undermines developmental structure of the society locally and internationally. All over the world today, cases of Illicit drug consumptions by the Nigeria youths has gained its momentum toward negative directions and its impact has degenerated to series of anti-behavioural problems such as trauma, larceny, egocentric suicide, cybercrime, kidnapping, laziness, terrorism, murdered cases, poor manpower supply and retrogressive national and international images among other nations in the world. Extant publications were reviewed for the study in line with broken theory by Keilling and Wilsons were also adopted for the justification of the inquiry. Mixed method and cross section Survey design and Yemane Yaro formula was adopted to select the 400 respondent for the quantitative inquiry but 245 questionnaires were found useful for the study while 10 in-depth interviews were carried out among the participants. The Chi-square result deciphers that youth access to illicit drug (X2)= 56.750a; p< 0.005.) Cost of purchasing of drug (X2)= 59.598a, p< 0.005.) and nature of employment (X2)=46.611, p<0.005.) of youths has significant relationship with violent behaviour. It is advisable youths to avoid joining drug related gangs; Nigeria Government should be willing to provide basic amenities for the youths so as to reduce violent activities in Nigeria